Magnetic and Compartmental Targeting of Azathioprine using Gelatin Microspheres: Formulation, Physicochemical Characterization and In Vitro Release Studies - Pinaparolu Devarajulu Arunkumar and Muniyandy Saravanan (Journal of Applied Pharmaceutical Science, 2013)
Azathioprine loaded gelatin microspheres were formulated to control/target drug release in an arthritic joint by magnetic force or intra-articular injection. Glutaraldehyde cross linked microspheres were characterized for drug loading, entrapment efficiency, gas chromatography, magnetite content, particle size, scanning electron microscopy (SEM), Fourier-Infrared spectroscopy (FT-IR), differential scanning calorimetry (DSC) and in vitro release studies. The gelatin microspheres loaded with azathioprine showed 17% of drug loading with 82% of entrapment efficiency. Gelatin magnetic microspheres showed 13% of loading with 87% of entrapment efficiency. Gas chromatography confirms absence of residual glutaraldehyde in the microspheres. The magnetite content of the azathioprine loaded gelatin magnetic microsphere was 25.7% w/w. The average particle sizes of gelatin nonmagnetic and magnetic microspheres were 41 and 54 µm, respectively. SEM confirms the spherical nature of the microspheres. FT-IR revealed the absence of drug polymer interaction, and DSC suggested amorphous nature of entrapped drug in the microspheres. The formulated microspheres could release the drug over a period of 48 h.
Keywords: Gelatin microspheres, magnetic microspheres, azathioprine, intra-articular, targeted drug delivery, controlled drug delivery.